Association between Infectious Disease and Hygiene Practice on Stunting Toddler Aged 24-59 Months - Natasya Putri Audiena; Marintan Laura Siagian (Amerta Nutrition, 2021)
Background : Child nutrition problem is still a major health problem in Indonesia. Toddlers are a period where children experience rapid growth and development, so they need a high nutrient. The problem of malnutrition can be identified from the children’s slow growth, one of which is in terms of body length or height. A condition where a children’s length or height is not optimal is called stunting. The incidence of stunting affected by several factors, such as infectious disease and bad hygiene practices.Method : The method of this study is observational research with case control research design. The sample of this study was grouped into two, case group and control group, with the number of each group is 28 respondents. The case group was a group of toodlers with stunting ages 24 – 59 months, while the control group was a group of toodlers ages 24 – 59 months with no stunting case. The study was conducted in Bulak Banteng Public Health work area from January -  May 2019. Data collection was carried out by collecting questionnaire about infectious disease and hygiene practices which were carried out by interview and observation method. Results : The result showed that there was an influence between the incidence of infectious disease (p=0,000) (OR= -3.402), and hygiene practices (p=0,000) (OR= -2.442) on stunting.Conclusion : The conclusion in this study is that there is a significant relationship between infectious diseases and hygiene practices with the incidence of stunting in toddler aged 24-59 months  (in Bulak Banteng Health Center, Surabaya).